2021
DOI: 10.20885/eksakta.vol2.iss2.art8
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Human Development Index and Percentage of Total Population on Poverty using OLS and GWR models in Central Java, Indonesia

Abstract: Central Java province is one of the provinces with the highest number of poor people on the island of Java, with the number of poor people in 2020 increasing by 0.44 million people from the previous year. Poverty is caused by several factors, one of which is the Human Development Index (HDI) and the Total Population level. Each region has different characteristics from other regions. These differences in characteristics cause more specific spatial effects, namely spatial heterogeneity. Geographically Weighted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
4
1
1
Order By: Relevance
“…The goodness of fit test of the GWR model with the fixed kernel tricube weighting function for modeling life expectancy in East Java Province shows that there is a statistical difference between the GWR model with the fixed kernel tricube weighting function and the OLS regression model. The results of this study are not in line with research in Central Java Province which explains that there is no difference between the OLS regression model and the GWR model using fixed kernel tricube weighting function in modeling poverty [5]. The significant difference between the OLS model and the GWR model is caused by the presence of spatial weights with a range from 0 to close to 1 which are different at each location and cause the F statistic to get bigger and the p-value to get smaller.…”
Section: Discussioncontrasting
confidence: 92%
“…The goodness of fit test of the GWR model with the fixed kernel tricube weighting function for modeling life expectancy in East Java Province shows that there is a statistical difference between the GWR model with the fixed kernel tricube weighting function and the OLS regression model. The results of this study are not in line with research in Central Java Province which explains that there is no difference between the OLS regression model and the GWR model using fixed kernel tricube weighting function in modeling poverty [5]. The significant difference between the OLS model and the GWR model is caused by the presence of spatial weights with a range from 0 to close to 1 which are different at each location and cause the F statistic to get bigger and the p-value to get smaller.…”
Section: Discussioncontrasting
confidence: 92%
“…Several previous studies, such as those conducted by Mahara et al, have contributed to analyzing the impact of the Human Development Index (HDI) and the total population percentage on poverty in Central Java Province. The utilization of Ordinary Least Squares (OLS) and Geographically Weighted Regression (GWR) models in this research highlighted the increase in the number of impoverished people in Central Java Province in 2020, concluding that the GWR model, particularly with the Adaptive Kernel Bisquare weighting function, yielded superior results compared to the OLS model [22]. In line with this, Xindong's study in Sichuan Province, China, explored the relationship between poverty and geographic factors using OLS and GWR.…”
Section: Related Workmentioning
confidence: 62%
“…The GWR and OLS were employed in central java, Indonesia, to evaluate the impact of the human development index and population size on poverty. This study’s outcomes reported good performance of these models (Mahara and Fauzan 2021 ). The OLS and GWR methods are used to assess the influences of geographical parameters on forming land surface temperature (Kashki et al 2021 ).…”
Section: Introductionmentioning
confidence: 57%